(untitled) (Fractal: Journal of Psychology, 2010)
The article that is now presented reflects upon the History of madness, text that begins from Michel Foucault’s historical-archaeological analyses. Starting from a temporal writing which includes the period comprised between the Renaissance and Modernity, Foucault scrutinizes the distinct forms of the social perception of the mad person up to the institution of madness as a mental disease. An "archaeology of silence" to which madness is submitted, not a history of psychiatry, Foucault’s text questions about the historical conditions that favour the occurrence of psychiatry as a scientific discours about madness and the institution of the asylum as a place for the treatment of mad person.